1993
DOI: 10.1101/gad.7.4.570
|View full text |Cite
|
Sign up to set email alerts
|

Oct-2, although not required for early B-cell development, is critical for later B-cell maturation and for postnatal survival.

Abstract: Oct-2, a POU homeo domain transcription factor, is believed to stimulate B-cell-restricted expression of immunoglobulin genes through binding sites in immunoglobulin gene promoters and enhancers. To determine whether Oct-2 is required for B-cell development or function, or has other developmental roles, the gene was disrupted by homologous recombination. Oct-2 -/-mice develop normally but die within hours of birth for undetermined reasons. Mutants contain normal numbers of B-cell precursors but are somewhat de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
161
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(170 citation statements)
references
References 79 publications
9
161
0
Order By: Relevance
“…The availabil ity of homogeneous pre-BI cell populations differing only by the presence or absence of Pax5 made it possible to investigate whether BSAP regulates the expression of other known transcription factors. As shown by the RNase protection experiment in Figure 6, the expression of the transcription factors PU.l (Scott et al 1994), Ikaros (Georgopoulos et al 1994), EBF (Lin and Grosschedl 1995), E2A (Bain et al 1994;Zhuang et al 1994), Sox-4 (Schilham et al 1996), Oct-1 (Sturm et al 1988), Oct-2 (Corcoran et al 1993), and OBF-1 (Kim et al 1996;Schubart et al 1996) was unaffected at the mRNA level by the absence of Pax5. Similarly, the Pax5 mutation did nei ther influence transcription of the recombination acti vating genes RAG-1 (Schatz et al 1989) andRAG-2 (Oettinger et al 1990) nor expression of the germ-line tran script Ip which initiates within the IgH enhancer region (Lennon and Perry 1985).…”
Section: B-cell-specific Gene Expression In Pax5-deficient Pre-bi Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The availabil ity of homogeneous pre-BI cell populations differing only by the presence or absence of Pax5 made it possible to investigate whether BSAP regulates the expression of other known transcription factors. As shown by the RNase protection experiment in Figure 6, the expression of the transcription factors PU.l (Scott et al 1994), Ikaros (Georgopoulos et al 1994), EBF (Lin and Grosschedl 1995), E2A (Bain et al 1994;Zhuang et al 1994), Sox-4 (Schilham et al 1996), Oct-1 (Sturm et al 1988), Oct-2 (Corcoran et al 1993), and OBF-1 (Kim et al 1996;Schubart et al 1996) was unaffected at the mRNA level by the absence of Pax5. Similarly, the Pax5 mutation did nei ther influence transcription of the recombination acti vating genes RAG-1 (Schatz et al 1989) andRAG-2 (Oettinger et al 1990) nor expression of the germ-line tran script Ip which initiates within the IgH enhancer region (Lennon and Perry 1985).…”
Section: B-cell-specific Gene Expression In Pax5-deficient Pre-bi Cellsmentioning
confidence: 99%
“…However, a different situation prevails in fetal liver where PaxS is already required for full commitment to the B-lymphoid lineage. Progression of B-cell develop ment to the small pre-B-cell stage is furthermore depen dent on the function of the transcription factor Sox-4 (Schilham et al 1996), whereas Oct-2, OBF-1, and the pSO subunit of NF-KB have critical roles in the activation of mature B-cells to undergo plasma cell differentiation (Corcoran et al 1993;Sha et al 199S;Kim et al 1996;Schubart et al 1996). Importantly, the expression of none of these regulatory genes was affected in PaxS-de ficient pre-BI cells.…”
Section: Differential Dependency Of Fetal and Adult Pro-b-cell Develomentioning
confidence: 99%
“…43,44 However, genetic studies using knockout mice indicate that Oct-2 is dispensable for early B-cell development and does not affect the baseline expression of CD20 in immature B lymphocytes. 45 In our pilot experiments, HDAC inhibitors reduced the expressions of PU.1 and USF1 to nearly undetectable levels (data not shown). We therefore focused on the region harboring the binding sites of Sp1 and NF-kB (À726 to À315) in this study.…”
Section: Hdac Inhibitors Transactivate the Cd20 Gene Through Promotermentioning
confidence: 99%
“…Pit-1 function appeared to be critical for expression of pituitary-specific effector genes and for proliferation or survival of three anterior pituitary cell types (reviewed by Anderson and Rosenfeld (1994)). Oct-2 proved to serve a critical function in B-cell maturation (Corcoran et al, 1993), and the unc-86 gene product is important for lineage-dependent neuronal specification (Finney and Ruvkun, 1990). The role of Oct-1 during development, however, has remained elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Functions during embryonic development have been established for three of the initially identified POU domain proteins , i.e. for Pit-1, Oct-2 and Unc-86 (Finney and Ruvkun, 1990;Corcoran et al, 1993;Andersen and Rosenfeld, 1994), as well as for a number of more recently identified POU domain transcription factors Shimazaki et al, 1993;Takeda et al, 1994;Bhat et al, 1995;Nakai et al, 1995;Schonemann et al, 1995;Witta et al, 1995;Yeo et al, 1995). Pit-1 function appeared to be critical for expression of pituitary-specific effector genes and for proliferation or survival of three anterior pituitary cell types (reviewed by Anderson and Rosenfeld (1994)).…”
Section: Introductionmentioning
confidence: 99%